Tuning Surface Structure and Strain in Pd–Pt Core–Shell Nanocrystals for Enhanced Electrocatalytic Oxygen Reduction. Issue 7 (18th November 2016) - Xiong, Yalin; Shan, Hao; Zhou, Zhengnan; Yan, Yucong; Chen, Wenlong; Yang, Yaxiong; Liu, Yongfeng; Tian, He; Wu, Jianbo; Zhang, Hui; Yang, Deren
Abstract : Icosahedral, octahedral, and cubic Pd@Pt core–shell nanocrystals with two atomic Pt layers are epitaxially generated under thermodynamic control. Such icosahedra exhibit remarkably enhanced catalytic properties for oxygen reduction reaction compared to the octahedra and cubes as well as commercial Pt/C, which can be attributed to ligand and geometry effects, especially twin‐induced strain effect that is revealed by geometrical phase analysis.